Analisis Pola Konsumsi Makanan dan Non-Makanan di Kabupaten OKU - Putra, Firman Syah; Munajat, Munajat; Oktarina, Yetty; Primandari, Novegya Ratih (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the effect of household income, education level of the head of the household and number of family members on consumption patterns in OKU Regency. This research uses qualitative and quantitative descriptive analysis methods. The results of the analysis show that simultaneously household income, education of the head of the household and number of family members have a significant effect on the non-food consumption patterns of the community in OKU Regency. However, partially, household income and education of the head of the household have a significant effect on the non-food consumption patterns of the community in OKU Regency